Conductive powder containing copper as a main component, conductive paste, method for manufacturing electronic component, method for manufacturing conductive powder
Patent Information
- Application Number
- CN202580020525.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-24
- Filing Date
- 2025-03-10
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]然而,特别是在使用以铜为主成分的金属粉末在低氧气氛中进行烧制的情况下,难以适当地进行使粘合剂树脂等有机成分得以燃烧、分解、飞散的脱粘合剂
[0041] According to the present invention, a copper-based conductive powder and a method thereof are provided that are suitable for forming thin, dense, and highly continuous terminal electrodes even when fired at low temperatures. Additionally, a conductive paste capable of forming thin, dense, and highly continuous terminal electrodes even when fired at low temperatures is provided. Furthermore, a method for manufacturing electronic components having thin, dense, and highly continuous terminal electrodes even when fired at low temperatures is provided.
Smart Images

Figure FT_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to a copper-based conductive powder, a conductive paste using the conductive powder, a method for manufacturing electronic components using the conductive paste, and a method for manufacturing a copper-based conductive powder. In particular, it relates to materials suitable for forming terminal electrodes for multilayer ceramic electronic components such as multilayer ceramic capacitors, multilayer inductors, and multilayer piezoelectric actuators. Background Technology
[0002] Multilayer ceramic electronic components such as multilayer ceramic capacitors, multilayer inductors, and multilayer piezoelectric actuators are generally manufactured as described below.
[0003] First, a conductive paste for internal electrodes is printed in a given pattern on a barium titanate-based ceramic or other dielectric ceramic green sheet. Then, multiple sheets are stacked and pressed together to obtain an unfired laminate in which the ceramic green sheet and the internal electrode paste layer are alternately layered. The resulting laminate is then cut into chips of a given shape to obtain the laminate substrate. It should be noted that the laminate substrate is sometimes fired at high temperature at this point, and sometimes not at this point but simultaneously fired later along with the terminal electrode paste layer formed using the conductive paste for terminal electrodes. In this specification, regardless of the case, the laminate in its state before the formation of the terminal electrode paste layer is referred to as the "laminate substrate".
[0004] Then, by means of dip printing or other methods, the terminal electrode, which is composed of conductive powder, adhesive resin, organic solvent, glass frit, etc., is printed onto the exposed end of the internal electrode of the laminated substrate to form a conductive paste layer. After drying as needed, it is further fired at high temperature to form the terminal electrode.
[0005] Furthermore, sometimes nickel, tin, or other plating layers are formed on the terminal electrodes as needed through electroplating or other methods.
[0006] Previously, precious metals such as palladium, silver-palladium, and platinum were used as internal electrode materials. However, due to requirements for resource conservation and cost reduction, especially for sintered electrodes, there are requirements to prevent delamination and cracking caused by the oxidative expansion of palladium and silver-palladium during sintering. Therefore, in recent years, base metals such as nickel, cobalt, and copper have become the mainstream. Consequently, as terminal electrode materials, copper, nickel, cobalt, or their alloys, which readily form good electrical connections with base metal internal electrodes, are used to replace existing silver and silver-palladium materials.
[0007] In cases where base metals are used for both internal and terminal electrodes, to prevent these base metals from oxidizing during firing, the terminal electrodes are typically fired at a high temperature of 800°C in a non-oxidizing atmosphere with extremely low oxygen partial pressure, such as an inert gas atmosphere with an oxygen content of a few ppm to tens of ppm.
[0008] However, especially when using copper-based metal powder in a low-oxygen atmosphere for firing, it is difficult to properly debind the binder to allow organic components such as binder resins to burn, decompose, and disperse. If debinding is not sufficiently performed in the early, lower-temperature stages of firing, before the glass fluidization and copper powder sintering occur, carbon and organic residues will be trapped within the film after sintering begins. This can cause various problems such as gasification of organic decomposition products and blister formation at higher temperatures, which can impair the density of the fired film.
[0009] Therefore, how to efficiently remove the binder in the early stages of firing and reduce residual carbon before the sintering of copper powder in the high-temperature zone have been important issues for conductive pastes that use metal powders with base metals, especially copper.
[0010] As a technology to solve this problem, for example, Patent Document 1 discloses a conductive thick film composition comprising Cu powder, glass powder, and an organic carrier, wherein the Cu powder is composed of spherical powder and flake powder.
[0011] Existing technical documents
[0012] Patent documents
[0013] Patent Document 1: Japanese Patent Application Publication No. 8-180731 Summary of the Invention
[0014] The problem that the invention aims to solve
[0015] On the other hand, in recent years, in order to reduce environmental burden, lower manufacturing costs, and reduce thermal stress on the laminated substrate, it has been required to reduce the firing temperature when forming the aforementioned terminal electrodes. Furthermore, the miniaturization of electronic components necessitates thinner terminal electrodes. That is, it is required that the binder be properly removed before the copper powder is sintered, that densification be achieved through proper sintering even at low peak firing temperatures, and that thin terminal electrodes be formed.
[0016] However, the conductive paste described in Patent Document 1 was designed with the assumption of firing at a high temperature of 800°C in mind. Therefore, it is impossible to form terminal electrodes that meet the above requirements when firing at a low temperature of 720°C.
[0017] Therefore, an object of the present invention is to provide a copper-based conductive powder suitable for use in conductive pastes, and a method for manufacturing the same, wherein the conductive paste can form thin, dense, and highly continuous terminal electrodes even when fired at low temperatures. Furthermore, an object of the present invention is to provide a conductive paste capable of forming thin, dense, and highly continuous terminal electrodes even when fired at low temperatures. Additionally, an object of the present invention is to provide a method for manufacturing electronic components having thin, dense, and highly continuous terminal electrodes even when fired at low temperatures.
[0018] Problem Solving Methods
[0019] The inventors conducted repeated research to solve the above-mentioned problems and discovered that by using a copper-based conductive powder, a conductive paste suitable for forming thin, dense, and highly continuous terminal electrodes can be achieved even when sintered at low temperatures. This led to the completion of the present invention. The copper-based conductive powder exhibits a cumulative 50% particle size D50 of 0.3 μm or more and 4.5 μm or less in laser diffraction particle size distribution measurement, and its major axis X is relative to its median diameter. The ratio of the diameter Y is 1.0 or more and 3.0 or less, and the ratio of the major diameter X to the minor diameter Z is 1.5 or more and 5.0 or less, and at least one of (A), (B) and (C) below is satisfied: (A) the carbon content is 0.00% by mass or more and 0.10% by mass or less; (B) the TMA shrinkage rate at 400°C is 0% or more and less than 2%; (C) the average change in TMA shrinkage rate per unit temperature [% / °C] from 400°C to 700°C is 0.05 or more.
[0020] That is, the present invention (1) provides a conductive powder with copper as the main component, wherein the cumulative 50% particle size D50 of the volume reference in laser diffraction particle size distribution measurement is 0.3 μm or more and 4.5 μm or less. The ratio of the major diameter X to the median diameter Y, as defined below, of the aforementioned conductive powder is 1.0 or more and 3.0 or less, and the ratio of the major diameter X to the minor diameter Z, as defined below, is 1.5 or more and 5.0 or less. The above-mentioned conductive powder satisfies the following (A) and (B): (A) The carbon content is 0.00% by mass or more and 0.10% by mass or less; (B) The shrinkage rate of TMA as defined below is 0% or more and less than 2% at 400°C.
[0021] (Major diameter X and median diameter Y)
[0022] One hundred particles were randomly selected by scanning electron microscopy. The average length of the long side of the rectangle that circumscribed around each particle in a manner that minimizes the area was defined as the major diameter X, and the average length of the short side was defined as the median diameter Y.
[0023] (Short diameter Z)
[0024] 100 parts by weight of the conductive powder with copper as the main component were mixed with 7 parts by weight of acrylic resin dissolved in terpineol. The mixture was then kneaded using a three-roll mill, followed by dilution with terpineol, and adjusted to a temperature of 25°C and a shear rate of 4 seconds. -1 A paste composition was prepared by achieving a viscosity of 30 Pa·s. The paste composition was then cast onto a PET film using a coating device to form a coating film with a thickness of 250 μm. The coating film was dried in an atmospheric atmosphere at 150°C for 10 minutes to form a dried film. The cross-section of the dried film was exposed using an ion milling device. The cross-section of the dried film was observed using a scanning electron microscope. 100 particles were randomly selected, and the average length of the short side of the rectangle circumscribed around each particle in a manner that minimizes the area was defined as the minor diameter Z.
[0025] (TMA shrinkage rate)
[0026] After obtaining a sample by pressing 200 mg of the above-mentioned conductive powder with copper as the main component into a cylindrical shape with a diameter of 5 mm and a height of 2 mm for 3 minutes at a pressure of 1.0 kN, the sample was then heated from room temperature to 900 °C at a rate of 10 °C / min using a TMA device. The percentage (%) of the sample height relative to the sample height (2 mm) at each temperature was defined as the TMA shrinkage rate.
[0027] In addition, the present invention (2) provides a copper-based conductive powder of (1) that satisfies the following (C): (C) The average change in the above TMA shrinkage rate per unit temperature from 400°C to 700°C [% / °C] is 0.05 or more.
[0028] In addition, the present invention (3) provides a copper-based conductive powder of (1) or (2) with a TMA shrinkage rate at 600°C relative to the maximum TMA shrinkage rate of 0.73 or more.
[0029] In addition, the present invention (4) provides a conductive powder with copper as the main component as described in any one of (1) to (3), wherein the ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate at 700°C is 0.90 or more.
[0030] In addition, the present invention (5) provides a conductive powder with copper as the main component as described in any one of (1) to (4), wherein the ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate at 720°C is 0.94 or more.
[0031] In addition, the present invention (6) provides a copper-based conductive powder as described in any one of (1) to (5), wherein the tap density of the conductive powder as defined below exceeds 3.5 g / cm³. 3 .
[0032] (Tap density)
[0033] Measure 20g of the above-mentioned conductive powder, which is mainly composed of copper, and add it to a 20cm volume. 3 The container was compacted using a vibratory compaction device with a vibration stroke set to 20 mm and a compaction frequency set to 200 times. The density of the compacted sample was measured relative to its volume (cm³). 3 The value calculated in the form of the ratio of ) is defined as the tap density.
[0034] In addition, the present invention (7) provides a copper-based conductive powder as described in any one of (1) to (6), wherein the ratio of the crystallite diameter to the D50 is 6.0 × 10⁻⁶. -3 above.
[0035] In addition, the present invention (8) provides a conductive powder with copper as the main component as described in any one of (1) to (7), wherein at least a portion of the surface has an aliphatic amine.
[0036] In addition, the present invention (9) provides a conductive paste comprising: a copper-based conductive powder, a glass frit, an adhesive resin, and an organic solvent as described in any one of (1) to (8).
[0037] In addition, the present invention (10) provides a method for manufacturing an electronic component, comprising: a laminated substrate preparation step for preparing a laminated ceramic electronic component comprising a laminated substrate of a plurality of ceramic layers and a plurality of internal electrode layers; and a terminal electrode forming step for applying the conductive paste of (9) to the exposed end of the internal electrode of the laminated substrate, and then firing the applied conductive paste to form a terminal electrode.
[0038] In addition, the present invention (11) provides a method for manufacturing electronic components of (10), wherein the peak temperature of the above-mentioned firing is below 720°C.
[0039] In addition, the present invention (12) provides a method for manufacturing a conductive powder with copper as the main component, which is a method for manufacturing a conductive powder with copper as the main component as described in any one of (1) to (8), the manufacturing method comprising: a first step of preparing a raw material metal powder with copper as the main component generated by cooling molten copper-based metal droplets dispersed in the gas phase; and a second step of applying a physical force to the raw material metal powder with copper as the main component until the ratio of the major axis X to the minor axis Z reaches 1.5 or more and 5.0 or less.
[0040] The effects of the invention
[0041] According to the present invention, a copper-based conductive powder and a method thereof are provided that are suitable for forming thin, dense, and highly continuous terminal electrodes even when fired at low temperatures. Additionally, a conductive paste capable of forming thin, dense, and highly continuous terminal electrodes even when fired at low temperatures is provided. Furthermore, a method for manufacturing electronic components having thin, dense, and highly continuous terminal electrodes even when fired at low temperatures is provided. Attached Figure Description
[0042] Figure 1 This is a diagram illustrating the method for determining the minor diameter Z in this invention.
[0043] Symbol Explanation
[0044] 1. Cross-section of a conductive particle
[0045] 2. A rectangle of cross-section circumscribed in relation to a conductive particle.
[0046] 3. The shorter side of the rectangle
[0047] 4. The longer side of the rectangle Detailed Implementation
[0048] <Conductive powder with copper as the main component>
[0049] The conductive powder of the present invention, with copper as the main component, has a cumulative 50% particle size D50 in laser diffraction particle size distribution measurement based on a volume criterion of 0.3 μm or more and 4.5 μm or less, a major diameter X to median diameter Y ratio of 1.0 or more and 3.0 or less, and a major diameter X to minor diameter Z ratio of 1.5 or more and 5.0 or less. Furthermore, it satisfies (A) a carbon content of 0.00% by mass or more and 0.10% by mass or less, and (B) a TMA shrinkage rate of 0% or more and less than 2% at 400°C. Therefore, it is suitable for use in conductive pastes that can form thin, dense, and highly continuous terminal electrodes even when fired at low temperatures.
[0050] By using the aforementioned copper-based conductive powder in the conductive paste, the filling capacity of the conductive powder in the coated film of the conductive paste is improved. Therefore, even when firing at low temperatures, the sintering of the conductive powder is easier. Furthermore, the resin used in conductive pastes for terminal electrodes, especially those fired below 720°C, almost always undergoes thermal decomposition below 400°C. Since the aforementioned copper-based conductive powder is difficult to sinter up to 400°C, shrinkage can be suppressed, binder resin can be effectively removed, and carbon residue is less likely to remain during firing. Additionally, since sintering can easily proceed abruptly above 400°C, poor bubble formation at high temperatures is less likely, resulting in thin, dense, and highly continuous terminal electrodes.
[0051] It should be noted that the terms "major diameter X", "middle diameter Y", "minor diameter Z", and "TMA shrinkage rate" as specified in this specification (the present invention) are defined as follows.
[0052] (Major diameter X and median diameter Y)
[0053] One hundred particles were randomly selected by scanning electron microscopy. The average length of the long side of the rectangle that circumscribed around each particle in a manner that minimizes the area was defined as the major diameter X, and the average length of the short side was defined as the median diameter Y.
[0054] (Short diameter Z)
[0055] 100 parts by weight of the conductive powder with copper as the main component were mixed with 7 parts by weight of acrylic resin dissolved in terpineol. The mixture was then kneaded using a three-roll mill, followed by dilution with terpineol, and adjusted to a temperature of 25°C and a shear rate of 4 seconds. -1 A paste composition was prepared by achieving a viscosity of 30 Pa·s. The paste composition was then cast onto a PET film using a coating device to form a coating film with a thickness of 250 μm. The coating film was dried in an atmospheric atmosphere at 150°C for 10 minutes to form a dried film. The cross-section of the dried film was exposed using an ion milling device. The cross-section of the dried film was observed using a scanning electron microscope. 100 particles were randomly selected, and the average length of the short side of the rectangle circumscribed around each particle in a manner that minimizes the area was defined as the minor diameter Z.
[0056] (TMA shrinkage rate)
[0057] After obtaining a sample by pressing 200 mg of the above-mentioned conductive powder with copper as the main component into a cylindrical shape with a diameter of 5 mm and a height of 2 mm for 3 minutes at a pressure of 1.0 kN, the sample was then heated from room temperature to 900 °C at a rate of 10 °C / min using a TMA device. The percentage (%) of the sample height relative to the sample height (2 mm) at each temperature was defined as the TMA shrinkage rate.
[0058] use Figure 1 The method for determining the minor diameter Z is explained.
[0059] Figure 1 The image is obtained by observing the cross-section of the dried film obtained by drying the coated film using a scanning electron microscope.
[0060] Let the average length of the short side 3 of the rectangle whose area is minimized by the rectangle 2 of the cross section 1 circumscribed to the conductive particle be defined as the short diameter Z.
[0061] The conductive powder of the present invention only needs to be composed primarily of copper. It should be noted that, in this specification, "primary component" refers to a component that accounts for more than 50% by mass of the total, and particularly in conductive powders where copper is the primary component, it means that the copper content accounts for more than 50% by mass of all conductive powders, including mixed powders and alloy powders described later. The copper ratio in the conductive powder is preferably 80% by mass or more and 100% by mass or less, more preferably 90% by mass or more and 100% by mass or less, further preferably 95% by mass or more and 100% by mass or less, and particularly preferably 100% by mass (pure copper). By keeping the copper ratio in the conductive powder within the above range, the conductive powders can be easily sintered together, thus easily obtaining a dense sintered film.
[0062] It should be noted that the conductive powder in this invention only needs to be copper as the main component. It can be a mixture of copper powder and other elemental metal powders such as nickel powder and silver powder, or an alloy powder of copper and other elemental metals such as nickel and silver. In addition, it can be a composite powder formed by coating copper powder with glass, ceramics, etc., or it can be a powder with an oxide film on the surface. Furthermore, it can be a powder obtained by surface treatment using organometallic compounds, surfactants, etc., and two or more of these conductive powders can be mixed and used.
[0063] In this invention, the cumulative 50% particle size D50 of the copper-based conductive powder in laser diffraction particle size distribution measurement is only required to be 0.3 μm or more and 4.5 μm or less, more preferably 0.4 μm or more and 4.0 μm or less, even more preferably 0.5 μm or more and 3.5 μm or less, and particularly preferably 0.6 μm or more and 3.0 μm or less. By ensuring that the D50 of the copper-based conductive powder is within the above-mentioned range, sintering of the conductive powder is easy even when sintering is performed at low temperatures, making it easy to form a highly dense terminal electrode. Furthermore, it is easy to thin the terminal electrode layer.
[0064] In this invention, the ratio of the major diameter X to the median diameter Y of the copper-based conductive powder is only required to be 1.0 or more and 3.0 or less, preferably 1.0 or more and 2.5 or less. By ensuring that the ratio of the major diameter X to the median diameter Y of the copper-based conductive powder is within the above range, sintering is easy to perform even when sintering is carried out at low temperatures, and a dense sintered film is easily formed. In addition, it is easy to form a thin sintered film (terminal electrode) with excellent continuity.
[0065] It should be noted that the major diameter X and median diameter Y mentioned above can both be measured by observation using a scanning electron microscope. That is, 100 conductive particles can be randomly selected by observation using a scanning electron microscope, and the average length of the long side of the rectangle circumscribed around each particle in a manner that minimizes the area is measured as the major diameter X, and the average length of the short side is measured as the median diameter Y.
[0066] The ratio of the major axis X to the minor axis Z of the copper-based conductive powder of the present invention is only required to be 1.5 or more and 5.0 or less, preferably 1.5 or more and 4.5 or less, more preferably 1.5 or more and 4.0 or less, even more preferably 1.5 or more and 3.5 or less, further preferably 1.5 or more and 3.0 or less, and particularly preferably 1.5 or more and 2.5 or less. By ensuring that the ratio of the major axis X to the minor axis Z of the copper-based conductive powder is within the above-mentioned range, sintering is easily performed even when sintering is carried out at low temperatures, and a dense sintered film is easily formed. In addition, since shrinkage is suppressed, a thin sintered film (terminal electrode) with excellent continuity is easily formed. It should be noted that the aforementioned minor axis Z can be measured by scanning electron microscopy observation of the cross-section of a dried film formed using a paste composition containing the conductive powder of the present invention.
[0067] More specifically, 100 parts by weight of the conductive powder of the present invention and 7 parts by weight of acrylic resin (e.g., DIANAAL MB-2677 manufactured by Mitsubishi Chemical Corporation) dissolved in terpineol can be mixed, then kneaded using a three-roll mill (e.g., manufactured by Inoue Manufacturing Co., Ltd.), and then diluted with terpineol to adjust the temperature to 25°C and a shear rate of 4s. -1 A paste composition was prepared by achieving a viscosity of 30 Pa·s. The paste composition was then cast onto a PET film using a coating applicator to form a 250 μm thick coating film. The coating film was dried in an atmospheric atmosphere at 150°C for 10 minutes to form a dried film. The cross-section of the dried film was exposed using an ion milling device (e.g., IM4000 manufactured by Hitachi High-Tech Corporation). The cross-section of the dried film was observed using a scanning electron microscope (e.g., SU-8020 manufactured by Hitachi High-Tech Corporation). Based on this observation, 100 conductive particles were randomly selected, and the average length of the short side of the rectangle circumscribed to the conductive particles was measured and taken as the minor diameter Z.
[0068] The copper-based conductive powder of the present invention simultaneously satisfies the following conditions: (A) a carbon content of 0.00% by mass or more and 0.10% by mass or less, and (B) a TMA shrinkage rate of 0% or more and less than 2% at 400°C. Therefore, since sintering is difficult to perform up to 400°C, shrinkage can be suppressed and binder resin can be effectively removed. Furthermore, since the conductive powder itself has a low carbon content, carbon is less likely to remain during the sintering process. Additionally, since sintering can be easily and rapidly performed above 400°C, poor bubbling at high temperatures is less likely to occur, making it easier to form thin, dense, and highly continuous terminal electrodes.
[0069] The carbon content should be 0.00% by mass or more and 0.10% by mass or less, preferably 0.00% by mass or more and 0.08% by mass or less, more preferably 0.00% by mass or more and 0.06% by mass or less, even more preferably 0.00% by mass or more and 0.05% by mass or less, and particularly preferably 0.00% by mass or more and 0.04% by mass or less. This makes it easier to achieve the aforementioned effects. It should be noted that the carbon content (%) can be determined using a carbon / sulfur analysis apparatus (HORIBA, EMIA-320V).
[0070] The conductive powder with copper as the main component of the present invention has a TMA shrinkage rate of 0% or more and less than 2% at 400°C, preferably 0% or more and less than 1%, and particularly preferably 0%. Therefore, the above-mentioned effects can be obtained particularly significantly.
[0071] Preferably, the copper-based conductive powder of the present invention simultaneously satisfies all of the conditions described in (A), (B), and (C) below: (C) The average change in TMA shrinkage rate per unit temperature [% / °C] from 400°C to 700°C is 0.05 or more. Therefore, since sintering is difficult to perform up to 400°C, shrinkage can be suppressed and binder resin can be effectively removed. Furthermore, since the conductive powder itself has a low carbon content, carbon is less likely to remain during firing. Additionally, since sintering can be easily and rapidly performed above 400°C, poor bubbling at high temperatures is less likely to occur, making it particularly easy to form thin, dense, and highly continuous terminal electrodes. It should be noted that the upper limit of the above average change is not particularly limited; for example, it can be set to 0.5 or less.
[0072] The ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate of the copper-based conductive powder of the present invention at 720°C is preferably 0.94 or more, more preferably 0.95 or more, more preferably 0.96 or more, even more preferably 0.97 or more, and particularly preferably 1.0. Therefore, even when sintered at low temperatures, highly dense terminal electrodes can be easily formed.
[0073] It should be noted that the maximum TMA shrinkage rate in this specification (invention) refers to the maximum shrinkage rate among the TMA shrinkage rates measured at various temperatures by heating the conductive powder from room temperature to 900°C using the above-described method.
[0074] The ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate of the copper-based conductive powder of the present invention at 700°C is preferably 0.90 or more, more preferably 0.92 or more, more preferably 0.94 or more, more preferably 0.95 or more, even more preferably 0.96 or more, and particularly preferably 1.0. Therefore, even when sintered at low temperatures, it is easier to form a highly dense terminal electrode.
[0075] The ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate of the copper-based conductive powder of the present invention at 600°C is preferably 0.73 or more, more preferably 0.85 or more, further preferably 0.90 or more, and particularly preferably 0.93 or more. Therefore, even when sintered at low temperatures, it is particularly easy to form highly dense terminal electrodes.
[0076] The copper-based conductive powder of the present invention preferably has a TMA shrinkage rate of 16% or less, more preferably 15% or less, and particularly preferably 14% or less at 600°C. This facilitates the formation of thin and highly continuous terminal electrodes.
[0077] The copper-based conductive powder of the present invention exhibits a TMA shrinkage rate of 21% or less, more preferably 18% or less, further preferably 16% or less, and particularly preferably 15% or less at 700°C. This facilitates the formation of thin and highly continuous terminal electrodes.
[0078] The copper-based conductive powder of the present invention exhibits a TMA shrinkage rate of 22% or less, more preferably 18% or less, further preferably 16% or less, and particularly preferably 15% or less at 720°C. This facilitates the formation of thin and highly continuous terminal electrodes.
[0079] The copper-based conductive powder of the present invention exhibits a TMA shrinkage rate of 22% or less, more preferably 18% or less, further preferably 16% or less, and particularly preferably 15% or less at 800°C. This facilitates the formation of thin and highly continuous terminal electrodes.
[0080] The average change in TMA shrinkage rate per unit temperature [% / °C] of the copper-based conductive powder of the present invention from 400°C to 600°C is preferably 0.03 or more, more preferably 0.04 or more, more preferably 0.05 or more, more preferably 0.06 or more, and particularly preferably 0.07 or more. Therefore, even when sintered at low temperatures, it is easy to form a highly dense terminal electrode. It should be noted that the upper limit of the above-mentioned average change is not particularly limited, for example, it can be set to 0.5 or less.
[0081] The tap density of the copper-based conductive powder of the present invention preferably exceeds 3.5 g / cm³. 3 More preferably 3.7 g / cm³ 3 The above, and more preferably, is 3.9 g / cm³. 3 The above, and especially preferred, value is 4.1 g / cm³. 3 The above describes how thin and highly continuous terminal electrodes can be easily formed by keeping the tap density within the above range.
[0082] It should be noted that, for example, a tap density measuring device (SEISHIN ENTERPRISE Co., Ltd., KYT-4000) can be used to measure 20g of the copper-based conductive powder of the present invention and add it to a 20cm³ container. 3 In the test chamber, the compaction stroke was set to 20 mm and the number of compactions was set to 200. The result was measured by comparing the weight (g) of the compacted sample with the sample volume (cm³). 3 The tap density (g / cm³) was calculated in the form of the ratio of ) 3 ).
[0083] The crystallite diameter of the copper-based conductive powder of the present invention is preferably 17 nm or more, more preferably 18 nm or more, further preferably 19 nm or more, and particularly preferably 20 nm or more. By keeping the crystallite diameter within the above range, sintering is difficult to perform up to a certain temperature such as 400°C, thus shrinkage can be suppressed and binder resin can be effectively removed. Furthermore, since sintering is more likely to occur abruptly above 400°C, it is easier to form highly dense terminal electrodes. In addition, there is no particular limitation on the upper limit of the crystallite diameter; for example, it can be set to 25 nm or less, 24 nm or less, or 23 nm or less.
[0084] It should be noted that, for example, an XRD measurement device (manufactured by Rigaku Corporation, SmartLab) can be used to perform XRD measurements on diffraction angles 2θ: 20.0~100.0° under the conditions of tube voltage 40kV, tube current 30mA, step angle 0.01°, and scanning speed 10.0° / min. The peak corresponding to the (111) plane (around 43°) can be detected and the half width at half maximum (WWHM) can be measured. The crystallite diameter can then be calculated using the Scherrer formula.
[0085] The preferred ratio of the crystallite diameter to D50 of the copper-based conductive powder of the present invention is 6.0 × 10⁻⁶. -3 The above, and more preferably 7.0×10 -3 The above, and more preferably 8.0×10 -3 The above, and more preferably 9.0×10 -3 The above, and especially preferred, is 1.0 × 10 -2 The above describes how, by keeping the ratio of crystallite diameter to D50 within the aforementioned range, sintering is difficult to perform up to a certain temperature, such as 400°C. This suppresses shrinkage and effectively removes the binder resin. Furthermore, since sintering tends to occur abruptly above 400°C, highly dense terminal electrodes are easily formed. There is no particular upper limit to the ratio of crystallite diameter to D50; for example, it can be set to 1.0 × 10⁻⁶. -1 The following can also be set to 5.0×10 -2 The following can also be set to 3.0×10 -2 the following.
[0086] The conductive powder of the present invention, with copper as the main component, achieves a higher dry film density by keeping the ratio of the major axis X to the minor axis Z within the aforementioned range. Since a higher dry film density results in more suppressed shrinkage, this is preferred. It should be noted that the dry film density (g / cm³)... 3The following calculation can be performed: The above-mentioned paste composition is cast onto a PET film with a thickness of 250 μm to form a coated film. The coated film is dried in an atmospheric atmosphere at 100°C for 15 minutes, and then dried in an atmospheric atmosphere at 150°C for 15 minutes to form a dried film. The obtained dried film is cut into circles, and the weight and volume of the cut dried films are measured. The weight (g) is expressed as a percentage of the volume (cm³). 3 The density of the dry film (g / cm³) was calculated in the form of the ratio of 1 / 2 to 1 / 3. 3 ).
[0087] The copper-based conductive powder of the present invention preferably has a bottom surface and a surface opposite to the bottom surface, and can be shaped as follows: flat, cylindrical, elliptical cylindrical, frustum conical, elliptical frustum conical, cuboid, etc. Therefore, even when sintering at low temperatures, sintering is easy to perform, and a dense sintered film is easily formed. Furthermore, it is easy to form a thin sintered film (terminal electrode) with excellent continuity.
[0088] The bottom surface and the surface opposite to the bottom surface are preferably completely flat, but they may also have irregularities without impairing the effect of the invention. The average angle of the surface opposite to the bottom surface is preferably 0° or more and 45° or less, more preferably 0° or more and 30° or less, further preferably 0° or more and 15° or less, and particularly preferably 0°, i.e., parallel.
[0089] In this specification (the present invention), the side with the larger area of two opposing surfaces is designated as the "bottom surface," and the other surface is designated as the "surface opposite to the bottom surface." When the areas of the two opposing surfaces are the same, any chosen surface is designated as the "bottom surface," and the other surface is designated as the "opposite surface."
[0090] It should be noted that the conductive powder of the present invention does not exclude powders of other shapes such as spherical shapes, as long as the ratio of the major diameter X to the median diameter Y, the ratio of the major diameter X to the minor diameter Z, and D50 of the conductive powder as a whole meet the above-mentioned numerical range. In this case, there is no particular limitation on the content of conductive powder that meets the numerical range relative to the total conductive powder, preferably more than 50% by mass, more preferably 55% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more.
[0091] When the cumulative 10% particle size of the copper-based conductive powder of the present invention is defined as D10 and the cumulative 90% particle size is defined as D90 in the laser diffraction particle size distribution measurement, the ratio of (D90-D10) / D50 is preferably 7.5 or less, more preferably 6.5 or less, more preferably 5.0 or less, more preferably 4.0 or less, further preferably 3.0 or less, and particularly preferably 2.0 or less. The lower limit of (D90-D10) / D50 is not particularly limited; for example, it can be set to 0.2 or more.
[0092] By ensuring that the (D90-D10) / D50 of the copper-based conductive powder is within the aforementioned range, i.e., by narrowing the particle size distribution of the conductive powder, uniform sintering of the conductive powder can be achieved throughout the film. This suppresses localized sintering within the film, thus appropriately ensuring a debinding path throughout the film. Consequently, thin, dense terminal electrodes with excellent continuity can be formed. Furthermore, the thickening of the terminal electrode film caused by excessively large conductive powder particles can be suppressed.
[0093] The specific surface area of the copper-based conductive powder of the present invention is preferably 0.2 m². 2 / g or more and 3.0m 2 / g or less, preferably 0.3m 2 / g or more and 2.0m 2 / g or less. By ensuring that the specific surface area of the copper-based conductive powder is within the above range, sintering is easy to perform even when firing at low temperatures, and a dense fired film is easily formed. Furthermore, a thin fired film is easily formed.
[0094] The copper-based conductive powder of the present invention preferably has an aliphatic amine on at least a portion of its surface. By having an aliphatic amine on at least a portion of the surface of the copper-based conductive powder, oxidation of the copper-based conductive powder can be prevented while ensuring good dispersibility of the conductive powder in the paste. Therefore, the filling performance of the conductive powder of the present invention in the conductive paste coating film can be improved, thereby enabling the formation of a sintered film with excellent density even when sintered at low temperatures. Furthermore, since the conductive powder can be well dispersed in the conductive paste, it is easy to form thin and continuous terminal electrodes.
[0095] In this invention, the aliphatic amine is preferably 0.01 parts by mass or more and 1.0 parts by mass or less, more preferably 0.02 parts by mass or more and 0.10 parts by mass or less, further preferably 0.02 parts by mass or more and 0.08 parts by mass or less, and particularly preferably 0.02 parts by mass or more and 0.06 parts by mass or less, relative to 100 parts by mass of the copper-based conductive powder. By keeping the amount of aliphatic amine within the above range, the dispersibility of the conductive powder in the paste is improved, and the aliphatic amine is easily removed during firing. Therefore, it is easy to form thin, dense, and highly continuous terminal electrodes.
[0096] Examples of aliphatic amines used in this invention include: primary amines such as octylamine, laurylamine, myristicamine, stearylamine, oleylamine, tallow amine, and tallow propylenediamine; secondary amines such as distearate; and tertiary amines such as triethylamine, dimethyloctylamine, dimethylmyristicamine, dimethylpalmitoamine, dimethylstearylamine, dimethylbehenylamine, dimethyllaurylamine, and trioctylamine. Two or more of these amines can be used in combination, or a mixture of various aliphatic amines commercially available in the form of "aliphatic amines" can be used. In particular, from the perspective of ease of coating copper powder and adsorption to metals, alkylamines with a main chain of about 8 to 20 carbon atoms, or aliphatic amines with such alkylamines as the main component, are preferred.
[0097] <Method for manufacturing conductive powder with copper as the main component>
[0098] The conductive powder with copper as the main component of the present invention can be manufactured by the following method.
[0099] The method for manufacturing a copper-based conductive powder according to the present invention comprises: a first step of preparing a copper-based raw material metal powder generated by cooling molten copper-based metal droplets dispersed in a gas phase; and a second step of applying a physical force to the copper-based raw material metal powder until the ratio of the major axis X to the minor axis Z reaches 1.5 or more and 5.0 or less. This allows for the suitable manufacture of the copper-based conductive powder of the present invention.
[0100] [Step 1]
[0101] The first step in the manufacturing method of the present invention is the step of preparing a raw material metal powder with copper as the main component, which is generated by cooling molten copper-based metal droplets dispersed in the gas phase. There are no particular limitations on the method for preparing the raw material metal powder with copper as the main component generated by cooling molten copper-based metal droplets dispersed in the gas phase; for example, the following methods can be used.
[0102] That is, for example, in the first step described above, a copper-containing powder can be dispersed in the gas phase using a carrier gas. Then, the copper-containing powder dispersed in the gas phase is subjected to heat treatment at a temperature above the melting temperature of the copper-containing powder, thereby generating molten copper-based metal droplets dispersed in the gas phase. The metal droplets are then cooled to prepare the copper-based raw material metal powder.
[0103] Alternatively, for example, in the first step described above, at least a portion of a metal with copper as its main component can be heated to melt it and generate a molten metal. Then, the molten metal is dispersed in the gas phase to generate molten metal droplets with copper as its main component. The metal droplets are then cooled to prepare the raw material metal powder with copper as its main component.
[0104] Alternatively, for example, in the first step described above, at least a portion of a metal with copper as its main component can be heated to melt it and form a molten metal. Then, at least a portion of the molten metal is evaporated to generate metal vapor. The metal vapor is then cooled to form metal droplets, and the metal droplets are then cooled to prepare the raw metal powder with copper as its main component.
[0105] Alternatively, for example, in the first step described above, the solution containing copper salt can be sprayed to form droplets, and the droplets can be heat-treated at a temperature above the decomposition temperature of the copper salt and above the melting point of copper to generate molten copper-based metal droplets dispersed in the gas phase. Then, the metal droplets are cooled to prepare the raw material metal powder with copper as the main component.
[0106] Alternatively, for example, in the first step described above, a thermally decomposable metal compound powder containing copper can be dispersed in the gas phase using a carrier gas. Then, the thermally decomposable metal compound powder containing copper dispersed in the gas phase is subjected to heat treatment at a temperature above the thermal decomposition temperature and above the melting point of copper to generate molten copper-based metal droplets dispersed in the gas phase. The metal droplets are then cooled to prepare the raw material metal powder containing copper as the main component.
[0107] The carbon content of the copper-based raw material metal powder prepared in the first step is preferably 0.00% by mass or more and 0.10% by mass or less, preferably 0.00% by mass or more and 0.08% by mass or less, more preferably 0.00% by mass or more and 0.06% by mass or less, more preferably 0.00% by mass or more and 0.04% by mass or less, more preferably 0.00% by mass or more and 0.02% by mass or less, further preferably 0.00% by mass or more and 0.01% by mass or less, and particularly preferably 0.00% by mass. Therefore, in the second step described later, the copper-based conductive powder of the present invention can be readily obtained.
[0108] For the copper-based conductive powder of the present invention, it is preferable to prepare the copper-based raw material metal powder prepared in the first step by the above-described method (the so-called dry method). However, as long as the conductive powder obtained by the second step described later is the copper-based conductive powder of the present invention, there is no particular limitation on its manufacturing method, and the use of copper-based raw material metal powder prepared by the so-called wet method is not excluded.
[0109] [Step 2]
[0110] The second step in the manufacturing method of the present invention is the step of generating the conductive powder of the present invention with copper as the main component. In this second step, a physical force is applied to the raw material metal powder with copper as the main component until the ratio of the major diameter X to the minor diameter Z reaches 1.5 or more and 5.0 or less.
[0111] A method for applying physical force to a copper-based raw material metal powder until the ratio of its major diameter (X) to its minor diameter (Z) reaches 1.5 or more and 5.0 or less can be exemplified by mixing a medium, the copper-based raw material metal powder prepared in the first step, a solvent, and a lubricant as needed, and then applying physical force to the copper-based raw material metal powder using the aforementioned medium until the ratio of its major diameter (X) to its minor diameter (Z) reaches 1.5 or more and 5.0 or less. Examples of such a medium include beads and spheres. An example of a medium size is a diameter of 0.1 mm.
[0112] The material of the medium is not particularly limited; for example, zirconium oxide can be used. The solvent is also not particularly limited; for example, sec-butanol can be used. The lubricant is also not particularly limited; fatty acids and aliphatic amines can be used, with aliphatic amines being preferred. By adjusting the size, material, type of solvent, type of lubricant, and the flow rate and number of passes (residence time) of the mixture of the medium shown above, the shape of the copper-based conductive powder generated in this process can be controlled within a suitable range.
[0113] The method for manufacturing the conductive powder with copper as the main component of the present invention only requires the first step and the second step described above. Other steps may be added before the first step, between the first step and the second step, or after the second step.
[0114] <Conductive Paste>
[0115] The conductive paste of the present invention comprises: the copper-based conductive powder of the present invention described above, glass frit, adhesive resin, and organic solvent.
[0116] For the conductive paste of the present invention, it is preferable to coat the conductive paste onto a laminated substrate or the like to form a coating film, and then dry the coating film as needed to form a dried film before firing it for use. There is no particular limitation on the peak firing temperature; firing at 600°C or higher, which is lower than existing firing temperatures, is acceptable. From the viewpoint of reducing environmental impact, lowering manufacturing costs, and reducing thermal stress on the laminated substrate, 600°C or higher and 720°C or lower is preferred, and particularly preferred is 600°C or higher and 700°C or lower.
[0117] <Glass Material>
[0118] In this invention, the cumulative 50% particle size D50 of the glass frit in laser diffraction particle size distribution measurement is preferably 0.3 μm or more and 2.0 μm or less, more preferably 0.5 μm or more and 1.5 μm or less. By keeping the D50 of the glass frit within the above range, it is easy to form a dense sintered film, and in addition, it is easy to form a sintered film (terminal electrode) with excellent continuity.
[0119] When the cumulative 10% particle size of the glass frit in the laser diffraction particle size distribution measurement of the present invention is set as D10 and the cumulative 90% particle size is set as D90, the ratio of (D90-D10) / D50 is preferably 7.5 or less, more preferably 6.5 or less, more preferably 5.0 or less, further preferably 3.5 or less, and particularly preferably 2.5 or less. The lower limit of (D90-D10) / D50 is not particularly limited; for example, it can be set to 0.2 or more.
[0120] By ensuring that the (D90-D10) / D50 of the glass frit is within the aforementioned range—that is, by ensuring a narrow particle size distribution of the glass frit—uniformly distributed glass frit of uniform size is uniformly distributed within the film before firing, which is densely filled with conductive powder. Therefore, the conductive powder can be easily and uniformly sintered throughout the film. Furthermore, since this suppresses localized sintering within the film, a suitable debonding path can be ensured throughout the film, resulting in the formation of thin, dense, and highly continuous terminal electrodes. By minimizing the amount of very small glass frit that is agglomerated and prone to softening / flowing, localized sintering and the resulting poor debonding are easily suppressed. Additionally, by minimizing the amount of very large glass frit, exposure of the laminated substrate due to voids generated at the glass frit flow points during firing can be suppressed, thus improving the continuity of the terminal electrodes.
[0121] The composition of the glass material in this invention is not particularly limited. For example, glass based on BaO-ZnO system, BaO-ZnO-B2O3 system, RO-ZnO-B2O3-MnO2 system, RO-ZnO system, RO-ZnO-MnO2 system, RO-ZnO-SiO2 system, ZnO-B2O3 system, SiO2-B2O3-R'2O system, SiO2-RO-R'2O system (where R is an alkaline earth metal element and R' is an alkali metal element) can be used.
[0122] The glass transition temperature of the glass frit in this invention is preferably 400°C or higher and 550°C or lower. By keeping the glass transition temperature of the glass frit within this range, the glass can easily wet and spread in the film even when firing at low temperatures, thus facilitating the formation of a dense fired film. Furthermore, since wetting and spreading are difficult below 400°C, by combining it with the copper-based conductive powder of this invention, which is difficult to sinter up to 400°C and can suppress shrinkage, residual carbon is significantly reduced. As a result, defects such as bubble formation are less likely to occur, making it easier to form thin, dense, and highly continuous terminal electrodes, which is therefore preferred. Additionally, by also combining it with the binder resin, which can suitably undergo thermal decomposition below 400°C (described later), the above effects become more pronounced, making it particularly easy to form thin, dense, and highly continuous terminal electrodes, which is also preferred.
[0123] The softening point of the glass frit in this invention is preferably 500°C or higher and 650°C or lower. By keeping the softening point of the glass frit within the above range, the glass can easily wet and spread in the film even when firing at a low temperature, thus making it easy to form a dense fired film.
[0124] The specific surface area of the glass frit in this invention is preferably 2.0 m². 2 / g or more and 7.0m 2 / g or less, preferably 3.0m 2 / g or more and 6.0m 2 / g or less. By keeping the specific surface area of the glass frit within the above range, the glass frit can be easily and uniformly dispersed in the film, thus making it easy to form a dense sintered film.
[0125] In this invention, the amount of glass frit relative to 100 parts by mass of conductive powder is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 4 parts by mass or more and 18 parts by mass or less, even more preferably 6 parts by mass or more and 16 parts by mass or less, and particularly preferably 8 parts by mass or more and 14 parts by mass or less. By keeping the amount of glass frit within the above range, a dense sintered film can be easily formed.
[0126] <Adhesive Resin>
[0127] The adhesive resin used in this invention is not particularly limited, but acrylic resin is preferred. The ratio of acrylic resin to the total adhesive resin is preferably more than 50% by mass, more preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more. When acrylic resin is used, its thermal decomposition in a nitrogen atmosphere is excellent, thus allowing for effective removal of the adhesive resin without causing oxidation of copper.
[0128] For the adhesive resin of the present invention, thermogravimetric analysis (heating at 10°C / min in a nitrogen atmosphere) shows a weight reduction of at least 98% by mass, more preferably at least 99% by mass, and particularly preferably at least 100% by mass at temperatures below 400°C. The adhesive resin of the present invention can be a combination of two or more types, but regarding the above-mentioned thermogravimetric analysis, it is preferred that the resin as a whole is within the above-mentioned range. As described above, by combining the above-mentioned adhesive resin, which suitably undergoes thermal decomposition below 400°C, with the copper-based conductive powder of the present invention, which is difficult to sinter up to 400°C and whose shrinkage can be suppressed, residual carbon is significantly reduced. As a result, poor bubble formation is less likely, and therefore, it is easier to form thin, dense, and highly continuous terminal electrodes, which is particularly preferred.
[0129] The amount of adhesive resin in this invention is not particularly limited, but is preferably 3 parts by mass or more and 11 parts by mass or less, more preferably 4 parts by mass or more and 10 parts by mass or less, even more preferably 5 parts by mass or more and 9 parts by mass or less, and particularly preferably 6 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of conductive powder. By keeping the amount of adhesive resin within the above range, it is easy to form thin, dense terminal electrodes with excellent continuity.
[0130] The weight-average molecular weight of the acrylic resin used in this invention is not particularly limited; for example, acrylic resins with a weight-average molecular weight of 20,000 or higher and a weight-average molecular weight of 1,000,000 or lower can be used. It should be noted that two or more acrylic resins with different weight-average molecular weights, structures, etc., can be used in combination.
[0131] <Organic Solvents>
[0132] The organic solvents used in this invention are not particularly limited, and examples include terpineol, dihydroterpineol, dihydroterpineol acetate, sec-butanol, butylcarbitol, butylcarbitol acetate, benzyl alcohol, etc.
[0133] <Additives>
[0134] Provided that the effects of the present invention are not impaired, the conductive paste of the present invention may, in addition to the above-mentioned components, contain additives such as defoamers, plasticizers, dispersants, and rheology modifiers as needed. Examples of plasticizers include dimethyl phthalate, diethyl phthalate, dibutyl phthalate, di-2-ethylhexyl phthalate, di-n-octyl phthalate, butyl benzyl phthalate, dioctyl adipate, diisononyl adipate, dibutyl sebacate, diethyl sebacate, dioctyl sebacate, tricresyl phosphate, chlorinated paraffin, and diisononyl cyclohexane-1,2-dicarboxylic acid. Examples of rheology modifiers include, for example, silica powder.
[0135] <Physical Properties of Conductive Paste>
[0136] The shear rate of the conductive paste of the present invention was measured at 25°C in 4s. -1 There are no particular limitations on the viscosity, but it is preferably 10.0 Pa·s or more and 80.0 Pa·s or less, and particularly preferably 20.0 Pa·s or more and 60.0 Pa·s or less. By keeping the viscosity of the conductive paste within the above range, it is easy to form thin, dense terminal electrodes with excellent continuity.
[0137] The conductive paste of the present invention exhibits a shear rate of 0.4 s when measured at 25°C. -1 The viscosity at 40s relative to the shear rate -1 There are no particular limitations on the viscosity ratio, but it is preferably 2.0 or higher and 20.0 or lower, and particularly preferably 3.0 or higher and 8.0 or lower. By keeping the viscosity ratio of the conductive paste within the above range, it is easy to form thin, dense terminal electrodes with excellent continuity.
[0138] When a strain of 1% is applied to the conductive paste of the present invention at an angular frequency of 1 Hz, the value of the phase difference δ between the strain and the stress generated by the strain is not particularly limited, but is preferably 45° or more and 80° or less, and particularly preferably 45° or more and 78° or less. By keeping the value of the phase difference δ of the conductive paste within the above range, it is easy to form thin, dense terminal electrodes with excellent continuity.
[0139] For the conductive paste of the present invention, for example, an evaluation test sample prepared by the method described below can be used to calculate the electrode area ratio of the terminal electrode, the average value of the maximum thickness of the terminal electrode, and the average value of the minimum thickness of the terminal electrode, as described later.
[0140] The test specimens for evaluation can be prepared as follows: For example, a multilayer substrate consisting of a cuboid-shaped dielectric layer containing barium titanate and an internal electrode layer containing nickel, with a length of 0.6 mm, a width of 0.3 mm, and a height of 0.3 mm, is prepared. The descent speed of the multilayer substrate is set to 300 μm / s, and the lifting speed is set to 100 μm / s. The conductive paste is applied to the exposed ends of the internal electrodes of the multilayer substrate using an dip-printing method. Then, the substrate is kept in an atmospheric atmosphere at 150°C for 10 minutes. Then, the temperature is increased at a rate of 50°C / min in a nitrogen atmosphere, and held at 700°C for 15 minutes to form terminal electrodes. This process is used to fabricate 20 electronic components with terminal electrodes. Each of the 20 electronic components is then embedded in resin. For each electronic component, it is cut along the stacking direction (perpendicular to the dielectric layer and the internal electrode layer) by passing through the central portion of both ends of the electronic component, thereby exposing the cross-section of each electronic component. This allows for the preparation of a sample for evaluation testing.
[0141] <Manufacturing Methods for Electronic Components>
[0142] The conductive paste of the present invention is suitable as a conductive paste for forming terminal electrodes in a laminated substrate for laminated ceramic electronic components.
[0143] The manufacturing method of an electronic component using the conductive paste of the present invention includes: a laminated substrate preparation step for preparing a laminated ceramic electronic component substrate composed of multiple ceramic layers and multiple internal electrode layers; and a terminal electrode forming step for coating the exposed ends of the internal electrodes of the laminated substrate with conductive paste, and then firing the coated conductive paste to form terminal electrodes.
[0144] By using the conductive paste of the present invention in the above-described method for manufacturing electronic components, thin, dense, and highly continuous terminal electrodes can be formed even when the terminal electrode forming process is carried out at a low temperature. In other words, according to the above-described method for manufacturing electronic components, electronic components having thin, dense, and highly continuous terminal electrodes can be manufactured even when the terminal electrode forming process is carried out at a low temperature.
[0145] The above-mentioned laminated substrate preparation process is the process of preparing the laminated substrate for laminated ceramic electronic components.
[0146] A laminated substrate for multilayer ceramic electronic components is composed of multiple ceramic layers and multiple internal electrode layers. In a laminated substrate for multilayer ceramic electronic components, the ceramic layers and internal electrode layers are alternately stacked. Examples of laminated substrates for multilayer ceramic electronic components include laminated substrates for multilayer ceramic capacitors, laminated substrates for multilayer ceramic inductors, and laminated substrates for piezoelectric actuators.
[0147] Examples of materials that form the ceramic layer of a laminated substrate for laminated ceramic electronic components include barium titanate, strontium titanate, calcium titanate, barium zirconate, strontium zirconate, calcium zirconate, and calcium strontium zirconate.
[0148] Examples of materials that can be used to form the internal electrode layer of a laminated substrate for laminated ceramic electronic components include any metal such as nickel, palladium, silver, copper, and gold, or alloys containing one or more of these metals (e.g., an alloy of silver and palladium).
[0149] The terminal electrode forming process is a process of forming a terminal electrode by applying the conductive paste of the present invention to the exposed end of the internal electrode of the laminated substrate for the laminated ceramic electronic component and firing the applied conductive paste.
[0150] There are no particular limitations on the coating method for the conductive paste; examples include dip printing, screen printing, and roller coating. Dip printing is preferred. It should be noted that the conductive paste can be dried after being coated onto the laminated substrate, and then fired.
[0151] In the terminal electrode forming process, a plating layer can be formed on the surface of the electrode after the terminal electrode has been formed.
[0152] It should be noted that, in this specification, both ends of the internal electrode exposed in the laminated substrate are designated as "ends," the side of the end in particular where the internal electrode is exposed is designated as the "end face," and the outer edge of the end face is designated as the "corner." Typically, in the terminal electrode forming process, when the conductive paste is applied to the ends, the conductive paste is applied in a manner that covers both the end face and the corner.
[0153] There are no particular limitations on the size of the laminated substrate using the conductive paste of the present invention. For example, it can be used in laminated substrates for 2012-sized, 1608-sized, 1005-sized, 0603-sized, 0402-sized, and 0201-sized laminated ceramic capacitors. In particular, for small laminated ceramic capacitors where thinner terminal electrodes are required, the conductive paste of the present invention can be suitably used in laminated substrates for 1005-sized, 0603-sized, 0402-sized, and 0201-sized laminated ceramic capacitors.
[0154] The electrode area ratio of the terminal electrodes of the laminated ceramic electronic components obtained by the present invention is not particularly limited, but is preferably 90% or more, and particularly preferably 99% or more. This makes it easier to prevent plating solution from penetrating the laminated substrate when plating the terminal electrodes. It should be noted that the above-mentioned electrode area ratio can be calculated, for example, by the following method: Twenty electronic components are resin-embedded separately, and each electronic component is cut along the lamination direction (perpendicular to the dielectric layer and the internal electrode layer) by passing through the central portion of each of its two end faces, thereby exposing the cross-section of each electronic component. Ten fields of view are observed on each cross-section of each electronic component using a scanning electron microscope, and the ratio of the electrode area in each field of view is calculated as the electrode area ratio.
[0155] The maximum thickness of the terminal electrode, measured by the method described later, is preferably 40 μm or less, more preferably 30 μm or less, more preferably 20 μm or less, further preferably 15 μm or less, and particularly preferably 10 μm or less. Furthermore, the average value of the maximum thickness of the terminal electrode calculated by the method described later is preferably 40 μm or less, more preferably 30 μm or less, more preferably 20 μm or less, further preferably 15 μm or less, and particularly preferably 10 μm or less. This allows for a reduction in the size of the laminated ceramic electronic component. Moreover, in a laminated ceramic electronic component of a given size, the thinner the terminal electrode layer, the larger the size of the laminated substrate can be, that is, the larger the electrode area and the number of layers can be, thus improving the performance of the laminated ceramic electronic component.
[0156] It should be noted that the method for measuring the maximum thickness described above is not particularly limited. For example, the electronic component can be resin-embedded, and the component can be cut along the lamination direction (perpendicular to the dielectric layer and the internal electrode layer) through the central portion of both ends of the electronic component, thereby exposing the cross-section of the electronic component. The cross-section can be observed using a scanning electron microscope. In this cross-section, when a perpendicular line is drawn from the outer periphery of the terminal electrode to the end face of the laminated substrate, the point where the length of the perpendicular line reaches its maximum is measured and taken as the maximum thickness. In addition, the method for calculating the average value of the maximum thickness described above is not particularly limited. For example, the maximum thickness of the terminal electrodes can be measured separately using the above method for 20 electronic components, and the average value of the maximum thickness of the terminal electrodes can be calculated.
[0157] The minimum thickness of the terminal electrode, as measured by the method described later, is preferably 1.0 μm or more, more preferably 2.5 μm or more, and particularly preferably 5.0 μm or more. Furthermore, the average value of the minimum thickness of the terminal electrode calculated by the method described later is preferably 1.0 μm or more, more preferably 2.5 μm or more, and particularly preferably 5.0 μm or more. Therefore, when plating the terminal electrode, it is easier to prevent the plating solution from penetrating the laminated substrate.
[0158] It should be noted that the method for determining the minimum thickness described above is not particularly limited. For example, the electronic component can be resin-embedded, and the component can be cut along the lamination direction (perpendicular to the dielectric layer and the internal electrode layer) through the central portion of both ends of the electronic component, thereby exposing the cross-section of the electronic component. The cross-section can be observed using a scanning electron microscope. In this cross-section, the thickness of the part where the length of the perpendicular line drawn from the outer periphery of the terminal electrode to the end face of the laminated substrate is the minimum, and the thickness of the part where the distance between the corner of the laminated substrate and the outer periphery of the terminal electrode is the shortest, are measured. The thickness of these thinnest parts is measured and taken as the minimum thickness. In addition, the method for calculating the average value of the minimum thickness described above is not particularly limited. For example, the minimum thickness of the terminal electrodes can be measured separately using the above method for 20 electronic components, and the average value of the minimum thickness of the terminal electrodes can be calculated.
[0159] Example
[0160] The present invention will now be described based on specific experimental examples, but the present invention is not limited to these experimental examples.
[0161] <Manufacturing of Copper Powder>
[0162] First, spherical copper powder manufactured by a known wet method (liquid-phase reduction method) and spherical copper powder manufactured by a known dry method (atomization method) were prepared as raw material powders. Next, zirconia beads with a diameter of 0.1 mm, the aforementioned spherical copper powder, sec-butanol, and a given lubricant (dimethylstearylamine) were mixed. Using a bead mill, the flow rate and pass count were appropriately adjusted to apply physical force to the spherical copper powder until the ratio of the major axis X to the minor axis Z reached the values in Table 1, thus obtaining the copper powders listed in Table 1. It should be noted that for the copper powders described in Experimental Examples 1 and 3, the above-described treatment was not performed, and the raw material powders were used directly. Additionally, in the experimental examples marked " The situation described is an experimental example outside the scope of this invention.
[0163] <D50>
[0164] The cumulative 10% particle size D50 (μm) on a volume basis was determined using a laser diffraction particle size distribution measuring device (HORIBA, LA-960).
[0165] <The ratio of major diameter X to median diameter Y and the ratio of major diameter X to minor diameter Z>
[0166] The ratios of major diameter X to median diameter Y and major diameter X to minor diameter Z were calculated using the values of major diameter X, median diameter Y, and minor diameter Z, which were determined by the method described below.
[0167] (Major diameter X and median diameter Y)
[0168] One hundred particles were randomly selected by scanning electron microscopy. The length of the longer side of the two orthogonal sides of the rectangle circumscribed around the particles in a manner that minimizes the area was measured and taken as the major diameter X. The length of the shorter side was measured and taken as the median diameter Y.
[0169] (Short diameter Z)
[0170] 100 parts by weight of copper powder and 7 parts by weight of acrylic resin (manufactured by Mitsubishi Chemical Corporation, DIANAAL MB-2677) dissolved in terpineol were mixed. Then, the mixture was kneaded using a three-roll mill (manufactured by Inoue Manufacturing Co., Ltd.). The mixture was then diluted with terpineol and adjusted to a temperature of 25°C and a shear speed of 4 seconds. -1A paste composition was prepared with a viscosity of 30 Pa·s. The paste composition was then cast onto a PET film using a coating applicator to form a 250 μm thick coating film. The coating film was dried in an atmospheric atmosphere at 150°C for 10 minutes to form a dry film. The cross-section of the dry film was exposed using an ion milling device (IM4000 manufactured by Hitachi High-Tech Corporation). The cross-section of the dry film was observed using a scanning electron microscope (SU-8020 manufactured by Hitachi High-Tech Corporation). Based on this observation, 100 copper particles were randomly selected, and the length of the shorter side of the two mutually orthogonal sides of the rectangle circumscribed around the particles in a manner that minimizes the area was measured. This shorter side was taken as the minor diameter Z.
[0171] <Crystal Diameter>
[0172] Using an XRD apparatus (Rigaku Corporation, SmartLab) and CuKα rays (wavelength λ: 1.5418 Å), XRD measurements were performed on diffraction angles 2θ: 20.0~100.0° under the conditions of tube voltage 40 kV, tube current 30 mA, step angle 0.01°, and scanning speed 10.0° / min. The peak corresponding to the (111) plane (around 43°) was detected and the half-width was measured. The crystallite diameter was calculated using the Scherrer formula.
[0173] <Tap density>
[0174] Using a tap density measuring device (SEISHIN ENTERPRISE Co., Ltd., KYT-4000), 20g of copper powder was measured and added to a 20cm³ volume. 3 In the test chamber, the compaction stroke was set to 20 mm and the number of compactions was set to 200. The result was measured by comparing the weight (g) of the compacted sample with the sample volume (cm³). 3 The tap density (g / cm³) was calculated in the form of the ratio of ) 3 ).
[0175] <Carbon content>
[0176] The carbon / sulfur analysis was performed using a HORIBA EMIA-320V analyzer.
[0177] <Shrinkage rate (thermomechanical analysis (TMA))>
[0178] 200 mg of copper powder was pressurized at 1.0 kN for 3 minutes to form a cylindrical shape with a diameter of 5 mm and a height of approximately 2 mm. The shrinkage rate (%) in the height direction of the sample was measured using a TMA apparatus (Bruker TMA4000S) under a nitrogen atmosphere, with the temperature increased from room temperature to 900 °C at a rate of 10 °C / min. It should be noted that the obtained value is rounded to the nearest decimal place and used as the shrinkage rate. For example, a value of -0.4% is considered a shrinkage rate of 0%, and a value of 1.4% is considered a shrinkage rate of 1%.
[0179] <Evaluation Test of Terminal Electrodes>
[0180] (Preparation of conductive paste)
[0181] 100 parts by weight of copper powder, 7 parts by weight of acrylic resin (manufactured by Mitsubishi Chemical Corporation, DIANALM-2677) dissolved in terpineol, and 10 parts by weight of glass frit (BaO-ZnO based glass) were mixed. The mixture was then kneaded using a three-roll mill (manufactured by Inoue Manufacturing Co., Ltd.), and then diluted with terpineol to adjust the temperature to 25°C and a shearing speed of 4 seconds. -1 The viscosity reached 30 Pa·s, and a conductive paste was prepared.
[0182] (Fabrication of electronic components with terminal electrodes)
[0183] A multilayer substrate was prepared, consisting of a barium titanate dielectric layer (0.6 mm in length, 0.3 mm in width, and 0.3 mm in height) and an internal electrode layer containing nickel. The substrate was lowered at a speed of 300 μm / s and raised at a speed of 100 μm / s. A conductive paste was applied to the exposed ends of the internal electrodes using an dip-printing method, and the substrate was held at 150°C for 10 minutes in an atmospheric atmosphere. Then, the substrate was heated to 700°C at a rate of 50°C / min in a nitrogen atmosphere and held for 15 minutes to form terminal electrodes, thus fabricating an electronic component with terminal electrodes.
[0184] (Preparation of test specimens for evaluation)
[0185] In each experimental example, 20 of the aforementioned electronic components were prepared. Each electronic component was resin-embedded, and for each electronic component, it was cut along the lamination direction (perpendicular to the dielectric layer and the internal electrode layer) by passing through the central portion of both ends of each electronic component, thereby exposing the cross-section of each electronic component to prepare an evaluation test specimen, and the evaluation was performed as shown below.
[0186] (Evaluation of the compactness (electrode area ratio) of terminal electrodes)
[0187] For the samples used in the evaluation test described above, 10 fields of view were observed for each sample using a scanning electron microscope, for a total of 200 fields of view. The ratio of the electrode area to the field of view was calculated as the electrode area ratio. The value of this electrode area ratio was evaluated based on the following evaluation criteria. It should be noted that an evaluation of A is considered acceptable.
[0188] A: Electrode area ratio is over 99%.
[0189] B: Electrode area ratio is above 90% and less than 99%.
[0190] C: Electrode area ratio less than 90%
[0191] (Evaluation of the film thickness of the terminal electrode)
[0192] The samples used in the evaluation tests were observed using a scanning electron microscope. The thickness of the thickest part (maximum thickness) and the thinnest part (minimum thickness) of the terminal electrode (sintered film) were measured. The average value of the maximum thickness and the average value of the minimum thickness were calculated for each test case. The average values of the maximum thickness and the average value of the minimum thickness were evaluated based on the following evaluation criteria. It should be noted that cases rated A and B were considered acceptable.
[0193] A: The average maximum thickness is ≤20μm, and the average minimum thickness is ≥2.5μm.
[0194] B: The average maximum thickness is ≤40μm and the average minimum thickness is ≥1.0μm (except for cases that meet the criteria in A above).
[0195] C: The average maximum thickness is >40μm, or the average minimum thickness is <1.0μm.
Claims
1. A conductive powder with copper as the main component, wherein the cumulative 50% particle size D50 in laser diffraction particle size distribution determination is greater than 0.3 μm and less than 4.5 μm on a volume basis. The conductive powder has a major diameter X ratio to median diameter Y of 1.0 or more and a median diameter Y of 3.0 or less, and a major diameter X ratio to minor diameter Z of 1.5 or more and a minor diameter Z of 5.0 or less. The conductive powder satisfies the following (A) and (B): (A) The carbon content is 0.00% by mass or more and 0.10% by mass or less; (B) The shrinkage rate of TMA as defined below is 0% or more and less than 2% at 400°C. (Major diameter X and median diameter Y) One hundred particles were randomly selected by scanning electron microscopy. The average length of the longest side of the rectangle circumscribed around each particle in a manner that minimizes the area was defined as the major diameter X, and the average length of the shortest side was defined as the median diameter Y. (Short diameter Z) 100 parts by weight of the conductive powder with copper as the main component were mixed with 7 parts by weight of acrylic resin dissolved in terpineol, and then the mixture was kneaded using a three-roll mill. The mixture was then diluted with terpineol and adjusted to a temperature of 25°C and a shear rate of 4 seconds. -1 A paste composition was prepared with a viscosity of 30 Pa·s. This paste composition was then cast onto a PET film using a coating device to form a 250 μm thick coating. The coating was dried at 150°C for 10 minutes in an atmospheric atmosphere to form a dried film. The cross-section of the dried film was exposed using an ion milling device and observed using a scanning electron microscope. One hundred particles were randomly selected, and the average length of the short side of the rectangle circumscribed around each particle in a manner that minimizes the area was defined as the minor diameter Z. (TMA shrinkage rate) After obtaining a sample by pressing 200 mg of copper-based conductive powder at a pressure of 1.0 kN for 3 minutes to form a cylindrical shape with a diameter of 5 mm and a height of 2 mm, the sample was then heated from room temperature to 900 °C at a rate of 10 °C / min using a TMA device in a nitrogen atmosphere. The percentage (%) of the sample height relative to the sample height (2 mm) at each temperature was defined as the TMA shrinkage rate.
2. The conductive powder with copper as the main component according to claim 1, wherein it satisfies the following (C): (C) The average change in the shrinkage rate of the TMA per unit temperature from 400°C to 700°C [% / °C] is 0.05 or more.
3. The conductive powder with copper as the main component according to claim 1, wherein the ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate at 600°C is 0.73 or higher.
4. The conductive powder with copper as the main component according to claim 1, wherein the ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate at 700°C is 0.90 or higher.
5. The conductive powder with copper as the main component according to claim 1, wherein the ratio of the TMA shrinkage rate to the maximum TMA shrinkage rate at 720°C is 0.94 or higher.
6. The conductive powder with copper as the main component according to claim 1, wherein, The tap density of this conductive powder, as defined below, exceeds 3.5 g / cm³. 3 , (Tap density) Measure 20g of the copper-based conductive powder and add it to a 20cm volume. 3 The container was compacted using a vibratory compaction device with a vibration stroke set to 20 mm and a compaction frequency set to 200 times. The density of the compacted sample was measured relative to its volume (cm³). 3 The value calculated in the form of the ratio of ) is defined as the tap density.
7. The conductive powder with copper as the main component according to claim 1, wherein the ratio of the crystallite diameter to the D50 is 6.0 × 10⁻⁶. -3 above.
8. The conductive powder with copper as the main component according to claim 1, wherein at least a portion of its surface contains aliphatic amines.
9. A conductive paste comprising: The conductive powder with copper as the main component as described in any one of claims 1 to 8 Glass material, Adhesive resin, and Organic solvents.
10. A method for manufacturing an electronic component, comprising: The laminated substrate preparation process involves preparing a laminated substrate for laminated ceramic electronic components, comprising multiple ceramic layers and multiple internal electrode layers; and In the terminal electrode forming process, the conductive paste as described in claim 9 is applied to the exposed end of the internal electrode of the laminated substrate, and then the applied conductive paste is fired to form the terminal electrode.
11. The method for manufacturing an electronic component according to claim 10, wherein, The peak firing temperature is below 720°C.
12. A method for manufacturing a copper-based conductive powder, comprising the method for manufacturing the copper-based conductive powder as described in any one of claims 1 to 8. The manufacturing method comprises: The first step involves preparing a copper-based raw material metal powder, generated by cooling molten copper-based metal droplets dispersed in the gas phase; and In the second step, a physical force is applied to the raw material metal powder, which is mainly composed of copper, until the ratio of the major diameter X to the minor diameter Z reaches 1.5 or more and 5.0 or less.
Citation Information
Patent Citations
Electroconductive thick film compound, thick film electrode, ceramic electronic component, and layered ceramic capacitor
JP1996180731A